Evaluation of decorativity of wooden bushes used in the greening of Saratov city - A. L. Kalmykova; G. N. Zaigralova; O. V. Azarova; I. A. Mnekina; A. E. Agapova; A. V. Khramchenko (Новые технологии)
The analysis of decorative features of woody shrubs on the objects of greening of general and limited use in Saratov is given. Periods of ornamental decorations are established depending on the phenological phases of shrubs. Types of shrubs are distributed according to the timing and duration of flowering. Analysis of the color range of flowers and inflorescences has revealed the dominant shades of flowering of shrubs. The types of shrubs are divided into groups according to the color of the autumn coloring of the leaves, and its seasonal changes are noted. The significance of the fruiting characteristics for improving the decorativeness of plantations during the autumn-winter period is substantiated. Recommendations are given to expand the range of shrub species to improve the aesthetic characteristics of urban green spaces.